Emotional Intelligence and Translation Studies: A New Bridge - Hubscher-Davidson, Séverine (Meta, 2013)
This paper presents a case for the study of non-cognitive psychological processes in Translation Studies (TS). More specifically, it aims to highlight the value of studying the emotional intelligence (EI) of translators and interpreters. Firstly, the concept of EI is defined and a review of trait EI profiling is undertaken, with a focus on two recent studies that have relevance for TS. Secondly, recent research within TS and related disciplines that provides evidence of the value of studying the affective and emotional traits of translators and interpreters is discussed. The final section of this paper provides some recommendations for the study of EI in TS research to benefit the translation and interpreting community. It will be argued that investigating emotional intelligence is both necessary and desirable to gain a deeper understanding of translation and interpreting processes.